Smooth-bark Mexican Pine (Pinus pseudostrobus) - Gary W. Knox (EDIS)
This beautiful pine is distinguished by long, pendulous needles that form a graceful, open evergreen conifer. The slender needles are up to 12 inches long in groups (fascicles) of five. In its native environment, smooth-bark Mexican pine is considered fast growing, and can reach more than 120 feet tall and about 60 feet wide. In southern Georgia, trees have reached heights of 32 feet and widths of 25 feet in 10 years. Trees have a pyramidal form when young, becoming flat-topped with age. In its native range, smooth-bark Mexican pine grows in temperate to warm temperate areas with predominately summer rainfall. Florida’s similar climatic conditions suggest that smooth-bark Mexican pine will adapt well throughout the state. Cold hardiness is not well-defined, but this species has grown well in southern Georgia (USDA Cold Hardiness Zone 8b). This 2-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, June 2014.